2014
DOI: 10.3844/jcssp.2014.178.189
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Multilingual Text- Independent Speaker Identification System

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The system performance was tested using a different length of segment. The experimental result showed that combination between DMFCC and MFCC features achieved better performance rate in comparison with using each one individually, where the Error Rate obtained for MFCC, DMFCC and (MFCC+ DMFCC) is 5.8%, 2.9% and 1.2% with MFCC respectively [21].…”
Section: Related Workmentioning
confidence: 94%
“…The system performance was tested using a different length of segment. The experimental result showed that combination between DMFCC and MFCC features achieved better performance rate in comparison with using each one individually, where the Error Rate obtained for MFCC, DMFCC and (MFCC+ DMFCC) is 5.8%, 2.9% and 1.2% with MFCC respectively [21].…”
Section: Related Workmentioning
confidence: 94%
“…Also, these models have the ability to form a smooth approximation to the arbitrarily-shaped observation densities in the absence of other information (Nidhyananthan and Kumari, 2013). With Gaussian mixture models, each sound is modeled as a mixture of several Gaussian clusters in the feature space.…”
Section: Gaussian Mixture Modelmentioning
confidence: 99%
“…Recently, ELMs have been widely used in fields such as computer vision, biomedical engineering, and control and robotics, because they are simple, efficient and have impressive performance [18], [19] [20] and [21]. ELMs have single layer hidden node parameters which are randomly generated.…”
Section: B Identifying Speakers Using Extreme Learning Machinementioning
confidence: 99%